Storm in a C-cup: A classic case of snowstorm appearance of the breast (Indian Journal of Case Reports, 2018)
Free silicone injection in breast though banned, is still practised in some countries by unscrupulous practitioners for breast augmentation. It is an entity which needs prompt identification and treatment. We hereby report a case of free silicone injection in breast highlighting the important role of imaging and classical mammographic and ultrasound appearance.